Academic Position in Medical Education Research - Donnon, PhD, Tyrone (Revue canadienne de l’éducation médicale, 2010)
The Office of Post Graduate Medical Education (PGME), together with the Medical Education and Research Unit (MERU), invites applications for a full-time academic position in medical education research at the Assistant or Associate Professor level.